Pain in Biblical texts and other materials of the ancient Mediterranean - Bauks, Michaela, 1962-; Olyan, Saul M. (Forschungen zum Alten Testament., 2021)
"This volume includes a wide range of studies on pain and its representation in texts and non-literary remains of the ancient Eastern Mediterranean, suggesting both the richness and complexity of the topic and the need for scholars to address it from a variety of perspectives. The essays engage the subject of pain and its representation in a multitude of ways, including consideration of the representation of physical pain, of psychological anguish, and the often complex relationship between the two. Several essays focus on the representation of pain in a particular genre of ancient literature such as Greek medical texts, narratives, prophetic texts, poetry, or legal texts. The volume also explores descriptions of concrete pain and the metaphorical use of pain imagery and idioms, as well as pain's relationship to shame, illness and torture. Finally, both communal and individual dimensions of pain are of interest to the contributors, as is the role pain might have had in ritual action and the part rites might play in the imposition of pain."--Publisher.